Cholinergic muscarinic M1 and M4 receptors as therapeutic targets for cognitive, behavioural, and psychological symptoms in psychiatric and neurological disorders. Issue 12 (December 2019) - Erskine, Daniel; Taylor, John-Paul; Bakker, Geor; Brown, Alastair J.H.; Tasker, Tim; Nathan, Pradeep J.
Highlights: The cholinergic system degenerates in many neuropsychiatric disorders. Cholinergic drugs typically increase all cholinergic activity. Targeting M1 and M4 receptors may more effectively treat the disorders discussed. Abstract : Cholinergic dysfunction is involved in a range of neurological and psychiatric disorders, including schizophrenia, dementia and Lewy body disease (LBD), leading to widespread use of cholinergic therapies. However, such drugs have focused on increasing the availability of acetylcholine (ACh) generally, with relatively little work done on the muscarinic system and specific muscarinic receptor subtypes. In this review, we provide an overview of the major cholinergic pathways and cholinergic muscarinic receptors in the human brain and evidence for their dysfunction in several neurological and psychiatric disorders. We discuss how the selectivity of cholinergic system dysfunction suggests that targeted cholinergic therapeutics to the muscarinic receptor subtypes will be vital in treating several disorders associated with cognitive dysfunction and behavioural and psychological symptoms.